2020
DOI: 10.4269/ajtmh.19-0551
|View full text |Cite
|
Sign up to set email alerts
|

Sanitation and Hygiene Practices in Small Towns in Tanzania: The Case of Babati District, Manyara Region

Abstract: Formative research findings from the fast-growing Babati town were used to assess the prevalence of sanitation and hygiene practices among individuals and institutions and associated factors. A cross-sectional study involving household surveys, spot-checks, focus group discussions, in-depth interviews, and structured observations of behaviors showed that 90% of households have sanitation facilities, but 68% have safely managed sanitation services. The most common types of household sanitation facilities were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…As a result, pour toilets and pit latrines are more commonly used in the study area. The findings from this study are similar to the findings from the studies conducted in India and Tanzania, which revealed more use of pour toilets and pit toilets than flush toilets due to the inaccessibility of the water system [ 33 - 34 ]. Therefore, the occurrence of diarrhoea is likely to be higher in households who use pour latrines and pit latrines than in others.…”
Section: Discussionsupporting
confidence: 88%
“…As a result, pour toilets and pit latrines are more commonly used in the study area. The findings from this study are similar to the findings from the studies conducted in India and Tanzania, which revealed more use of pour toilets and pit toilets than flush toilets due to the inaccessibility of the water system [ 33 - 34 ]. Therefore, the occurrence of diarrhoea is likely to be higher in households who use pour latrines and pit latrines than in others.…”
Section: Discussionsupporting
confidence: 88%
“…These factors were selected based on relevant literature. [27][28][29][30][31] The household wealth index was calculated by Principal Component Analysis following the World Food Program's Comprehensive Food Security and Vulnerability Analysis Guidelines. 32 Supplemental Table 2 lists the variables used to calculate the wealth index.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with previous studies, household infrastructure and wealth measured through a wealth index was an important factor in having water and soap at the handwashing station. 26,27 Taken together, our findings suggest that household infrastructure and water access challenges in this drought-prone setting should be considered when addressing hygienerelated behavior. 28 In particular, there should be an increased emphasis on addressing the needs of economically vulnerable groups through the development of, for example, pro-poor sanitation business models.…”
Section: Discussionmentioning
confidence: 71%